Sosialisasi dan Penyuluhan Kesehatan Penanganan Pertama Luka Terbuka Pada Anak Usia Dini - Tawil, Muh. Risal; Tarigan, Nanarita; Ali, St. Aminah; Fahamsya, Arifina; Alfiraza, Ery Nourika; Syahrir, Muhammad; Asmah, Nur (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Open wounds are a type of wound that is exposed to air due to skin damage without or accompanied by damage to the underlying tissue. Types of open wounds are abrasions (abrasion or excoriation), incised wounds or incised wounds (vulnus scissum), torn wounds (laceration or vulnus laceratum), stab wounds (vulnus punctum), bite wounds (vulnus morsum), gunshot wounds, burns (combustion). Early childhood are those who are in their growth period. During their growth period, it is not uncommon for them to be very active and explore new things. While exploring, some of them may fall, slip, get scratched and get wounds on their hands, foreheads or feet. The aim of community service is to provide education to the public about the types and procedures for initial treatment of wounds, as well as things that must be done and what must be avoided so that wound healing can be maximized. The method used is socialization and health education on the first treatment of open wounds in early childhood using observation and approaches through pre-test and post-test. The results achieved show that children's knowledge has increased and they know the steps for dealing with open wounds, which was proven during the question and answer session, children were able to mention how to handle open wounds in the correct order. The conclusion is that socialization of appropriate initial treatment is very necessary to prevent complications and speed up the wound healing process.